Flux Growth of Phosphide and Arsenide Crystals - Wang, Jian; Yox, Philip; Kovnir, Kirill (Frontiers in Chemistry, 2020)
Flux crystal growth has been widely applied to explore new phases and grow crystals of emerging materials. To accommodate the needs of high-quality single crystals, the flux crystal growth should be reliable, controllable, and predictable. The selections of suitable flux and growth conditions remain empirical due to lack of systematic investigation especially for reactions which involve highly volatile components, such as P and As. Considering the flux elements, often the system in question is a quaternary or a higher multinary system which drastically increases complexity. In this manuscript, on the examples of flux growth of phosphides and arsenides, guidelines of flux selections, existing challenges, and future directions are discussed. We expect that systematic development of this field by applying in-situ techniques and advances in machine-learning plus leveraging variables other than temperature, such as applied pressure, will make flux crystal growth a more powerful tool in the future.